Optimization of wind-solar-gas-storage integrated energy systems under the carbon and green certificate markets - Debin Fang; Heng Zhou; Pengyu Wang; Zeyu Xing (PLoS ONE, 2026)
This study investigates the optimization of wind-solar-gas-storage integrated energy systems (IES) under the dual-market mechanisms of carbon emission trading (CET) and green certificate trading (GCT). A unified analytical framework is developed to examine the techno-economic and environmental performance of IES within these combined market structures. The results indicate that the concurrent implementation of CET and GCT leads to a significant reduction in operational costs while simultaneously enhancing system sustainability. Through a series of scenario analyses, we explore the impact of price fluctuations in carbon and green certificate markets on system performance and compliance expenditures. Our findings indicate that the coordinated implementation of CET and GCT can significantly reduce the operating cost of integrated energy systems—by as much as 50.2%—while also effectively lowering carbon emissions by approximately 29.9%. An increase in the carbon price yields dual benefits of cost reduction and emission abatement, with a clearly identifiable economically efficient range between 0.05 and 0.20 CNY/kg. Although higher green certificate prices can further incentivize low-carbon operation, their marginal benefits tend to diminish beyond 80 CNY per certificate. These insights underscore the importance of integrated policy frameworks that leverage the synergistic effects of CET and GCT to optimize energy system performance. The study provides valuable guidance for policymakers, system operators, and stakeholders in the energy sector, highlighting the potential for strategic investments in these market mechanisms to achieve significant environmental and economic benefits.